INTERFERENSI MORFOLOGI PADA RUBRIK GAGASAN KORAN SOLOPOS SEBAGAI BAHAN AJAR ANALISIS ARTIKEL OPINI DI SMA - Widyawati, Susi; Rakhmawati, Ani; Sumarwati, Sumarwati (Universitas Hamzanwadi, 2022)
The aims of the study is to examine and describe: (1) the morphological interference, (2) the factors causing Javanese morphological interference into Indonesian in the Gagasan rubric of Solopos newspaper, and (3) the use of research results as teaching materials for analyzing language rules of Opinion Articles in SMA. The type of the research is qualitative research with a content analysis approach. The sources of data are using documents and informants. The sampling technique are purposive sampling, while the data collection technique used the reading and note taking technique. The data validity test technique used triangulation of data sources and triangulation of methods. The data analysis technique research is using interactive analysis. The results of the study indicate that the Gagasan rubric of Solopos Newspaper has (1) the morphological interference in the use of the prefix N, suffix / -an /, reduplication or rephrasing, affix removal, and exchange the suffix /-e/ BJ into the suffix /-nya/ BI (2) the causal factors Interference includes written language habits of journalistic variety, the author’s habits, the author's understanding of language interference and linguistic rules is lacking, the author's vocabulary is small, and researchers and editors are less careful, (3) the results of the study can be used and utilized in learning linguistic analysis of opinion articles. by students and teachers in high school. Keyword: Morphological Interference, Causative Factors, Teaching Materials